Structural basis for phosphatidylinositol phosphate kinase type Igamma binding to talin at focal adhesions. - de Pereda, J; Wegener, K; Santelli, E; Bate, N; Ginsberg, M; Critchley, DR; Campbell, I; Liddington, R (2005)
The cytoskeletal protein talin binds to a short C-terminal sequence in phosphatidylinositol phosphate kinase type Igamma (PIPKIgamma), activating the enzyme and promoting the local production of phosphatidylinositol 4,5 bisphosphate, which regulates focal adhesion dynamics as well as clathrin-mediated endocytosis in neuronal cells. Here we show by crystallographic, NMR, and calorimetric analysis that the phosphotyrosine binding (PTB)-like domain of talin engages the PIPKIgamma C terminus in a mode very similar to that of integrin binding. However, PIPKIgamma binds in the canonical PTB-peptide mode with an SPLH motif replacing the classic NPXY motif. The tighter packing of the SPLH motif against the hydrophobic core of talin may explain the stronger binding of PIPKIgamma. Two tyrosine residues flanking the SPLH motif (Tyr-644 and Tyr-649) have been implicated in the regulation of talin binding. We show that phosphorylation at Tyr-644, a Src phosphorylation site in vivo, has little effect on the binding mode or strength, which is consistent with modeling studies in which the phosphotyrosine makes surface-exposed salt bridges, and we suggest that its strong activating effect arises from the release of autoinhibitory restraints in the full-length PIPKIgamma. Modeling studies suggest that phosphorylation of Tyr-649 will likewise have little effect on talin binding, whereas phosphorylation of the SPLH serine is predicted to be strongly disruptive. Our data are consistent with the proposal that Src activity promotes a switch from integrin binding to PIPKIgamma binding that regulates focal adhesion turnover.